Pengaruh gel ekstrak induk kunyit (Curcuma longa linn) terhadap penyembuhan luka sayat pada tikus putih jantan (Rattus norvegicus) - Kaban, Vera Estefania; Nasri, Nasri; Rani, Zulmai; Suci, Nurul; Karo Sekali, Elva Swandi; Sagala, Hasel Untung Bersinar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
One plant that has been shown to aid wound healing is turmeric. Turmeric has been scientifically proven to have choleretic and anti-inflammatory properties. Turmeric contains curcumin, which has antibacterial and antioxidant qualities that can accelerate the migration and re-epithelialization of cells useful in wound healing, including myofibroblasts, fibroblasts, and macrophages. This study aimed to determine the effect of turmeric mother extract gel on wound healing in male white rats (Rattus norvegicus). This study was conducted using experimental tests. Turmeric extract was prepared using 96% ethanol solvent with a maceration process. A 2 cm long incision wound was made on the back of white rats. The test animals were then divided into five groups to receive different treatments. Groups 3, 4, and 5 received turmeric mother extract gel with concentrations of 1%, 5%, and 10%, while Group 1 was negative control and Group 2 was positive control. The results showed that the incision wounds in male white rats could heal faster - on average, about 7.10 days - when treated with 96% ethanol extract of turmeric mother with doses of 1%, 5%, and 10%. This study concludes that a 10% turmeric mother extract gel is the best method to accelerate wound healing.